Cultivating the masses : modern state practices and Soviet socialism, 1914-1939 - Hoffmann, David L. (David Lloyd), 1961- (Cornell paperbacks., 2011)
'Cultivating the Masses' examines the Russian Communist Party's pursuit of pronatal policies to boost the population, whilst at the same time ruthlessly executing, incarcerating and deporting.